RESEARCH ON ACOUSTIC LANDSCAPE OF LAKEFRONT TOURISM AREAS: A CASE STUDY OF HANGZHOU CITY, CHINA - JIANREN, SHI (ASEAN Journal on Hospitality and Tourism, 2007)
Urban open spaces are important for improvement in urban living quality. Traditional research on open spaces mainly focuses on spatial forms and visual esthetics to analyze environmental quality, but lacks of adequate consideration regarding acoustic elements. In the field of the acoustic environment, people pay much attention to interior sound quality design and noise pollution. In order to provide a new viewpoint for urban design and to reinforce design methods, herein, the concept of soundscape was introduced. In this survey, the types and the features of lakefront soundscapes, as well as visitorsâ spatial distribution were observed. 13 pairs of sound and image scenarios were presented to 112 subjects at a tourism city, Hangzhou, China. The sounds and images used were of real settings in lakefront scenic areas. Affective response was measured in terms of pleasure. Through the evaluation on the influence of the interaction between visual and acoustic stimuli on perception of the environment, it is proved that there is a need to identify places where the conservation of the sound environment is essential, due to the drastic impact of the loss of sound quality or its salient informational content on human appreciation, especially in theme spaces, and folk-custom landscapes. Moreover, the coherence between sound and image influences human preferences, since coherent combinations are rated higher than the mean of the component stimuli. As a result, the spatial partition of soundscape is also necessary with the movement of the visual images. Finally, some design guidelines regarding soundscape are proposed with the illustrations of four typical lakefront spots.